Impact-resistant modified PETG polyester material and preparation method thereof

By mixing PETG resin and other modifiers and modifying wear-resistant and corrosion-resistant additives, the lack of performance of PETG polyester materials under impact, friction and corrosion conditions is solved, and the impact, wear and corrosion resistance of the material is significantly improved, which extends the service life and reduces maintenance costs.

CN119662001AInactive Publication Date: 2025-03-21HENAN YUANHONG POLYMER NEW MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510197987.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-21
Publication Date
2025-03-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

PETG polyester material exhibits insufficient impact resistance, poor wear resistance and poor corrosion resistance under conditions such as external force impact, friction and chemical corrosion, which limits its application in outdoor billboards, automotive interiors, mechanical transmission parts and other fields.

Method used

By scientifically disposing of the proportion of PETG resin, impact modifier, wear-resistant enhancer, stabilizer, lubricant, corrosion-resistant additive and antioxidant, and innovatively modify the wear-resistant enhancer and corrosion-resistant additive, the internal structure and intermolecular force of the material are optimized, thereby improving the impact, wear and corrosion resistance of the material.

Benefits of technology

It significantly improves the impact resistance, wear resistance and corrosion resistance of PETG polyester materials, extends the service life of the material, reduces maintenance and replacement costs, and maintains good performance stability in high temperature and oxidation environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of PETG polyester materials, and particularly discloses an impact-resistant modified PETG polyester material and a preparation method thereof, and the impact-resistant modified PETG polyester material comprises the following components: 50-80 parts of PETG resin, 10-30 parts of an impact-resistant modifier, 5-15 parts of a wear-resistant reinforcing agent, 1-5 parts of a stabilizer, 1-3 parts of a lubricant, 2-8 parts of a corrosion-resistant additive, and 1-3 parts of an antioxidant. The impact modifier is formed by compounding a methyl methacrylate-butadiene-styrene copolymer, an acrylonitrile-butadiene-styrene copolymer and an ethylene-octene copolymer according to a compounding ratio of 1: 1: 3, and the wear-resistant enhancer is formed by compounding ultra-high molecular weight polyethylene micro powder, nano ceramic particles and polytetrafluoroethylene micro powder. The compounding ratio range is 1: 1: 2. According to the impact-resistant modified PETG polyester material and the preparation method thereof, the impact-resistant modified PETG polyester material has relatively good impact resistance, wear resistance, corrosion resistance and oxidation resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of PETG polyester materials, in particular to an impact-resistant modified PETG polyester material and a preparation method thereof. Background Art

[0002] As a new type of thermoplastic polyester, PETG polyester material has been widely used in many fields such as packaging, electronics, medical treatment, and architectural decoration due to its excellent transparency, good processing performance, and non-toxic and environmentally friendly characteristics. For example, in the packaging field, containers made of PETG materials can clearly display the contents and attract consumers' attention; in the electronics field, its good processing performance makes it suitable for manufacturing various electronic equipment shells. However, with the rapid development of various industries and the continuous advancement of technology, the performance requirements for PETG polyester materials are becoming increasingly stringent. In practical applications, PETG polyester materials have exposed some performance shortcomings. In some application scenarios that need to withstand external force impact, such as outdoor billboards, automotive interior parts, etc., ordinary PETG polyester materials have insufficient impact resistance and are easily broken and damaged when impacted, which limits their further application. In terms of wear resistance, when used to manufacture some parts that have long-term friction with other objects, such as mechanical transmission parts, conveying pipelines, etc., ordinary PETG polyester materials wear quickly, resulting in a shorter service life and increased maintenance and replacement costs. At the same time, in the face of chemical corrosion environments, such as chemical equipment, marine engineering facilities, etc., ordinary PETG The corrosion resistance of polyester materials is difficult to meet the requirements. They are easily corroded by chemicals such as acids, alkalis, and salts, resulting in decreased material performance and damaged appearance. In addition, under high temperature, light and other conditions, the oxidation resistance of ordinary PETG polyester materials is poor, and oxidation aging is prone to occur, causing the material to become brittle and performance to deteriorate, affecting the long-term stability of the product. In order to overcome these problems and meet the needs of various industries for high-performance materials, R&D personnel are committed to modifying PETG polyester materials by adjusting the formula composition, adding impact modifiers, wear-resistant enhancers, stabilizers, lubricants, corrosion-resistant additives and antioxidants, and optimizing the preparation process. As shown in the different embodiments in the table, we continue to explore ways to improve the comprehensive performance of PETG polyester materials to promote its application and development in more fields. Summary of the invention

[0003] To achieve the above purpose, the present invention is implemented by the following technical scheme: an impact-modified PETG polyester material and a preparation method thereof, comprising the following components: 50-80 parts of PETG resin, 10-30 parts of impact modifier, 5-15 parts of wear-resistant enhancer, 1-5 parts of stabilizer, 1-3 parts of lubricant, 2-8 parts of corrosion-resistant additive, and 1-3 parts of antioxidant.

[0004] Preferably, the impact modifier is a compound of methyl methacrylate-butadiene-styrene copolymer, acrylonitrile-butadiene-styrene copolymer and ethylene-octene copolymer, and the compounding ratio range is 1:1:3.

[0005] Preferably, the wear-resistant enhancer is a compound of ultra-high molecular weight polyethylene micropowder, nano-ceramic particles and polytetrafluoroethylene micropowder, and the compounding ratio ranges from 1:1:2.

[0006] Preferably, the stabilizer is an organic tin stabilizer, and the lubricant is ethylene bisstearamide.

[0007] Preferably, the corrosion-resistant additive is a compound of fluorine-containing polymer, nano-silicon dioxide and phosphate compound, and the compounding ratio is 1:1:3.

[0008] Preferably, the wear-resistant enhancer can also be replaced by a modified wear-resistant enhancer, and the preparation process of the modified wear-resistant enhancer includes: The compounded wear-resistant reinforcing agent is mixed with carbon nanotubes accounting for 2-6% of its total mass, and mixed for 20-30 minutes at 100-130°C and a screw speed of 180-250r / min. The carbon nanotubes have extremely high strength and modulus, and can form a three-dimensional reinforcement network in the wear-resistant reinforcing agent system, significantly improving the material's ability to resist wear; The wear-resistant reinforcing agent after the first modification is subjected to plasma treatment. Under the conditions of RF power of 120-180W and treatment time of 15-25 minutes, more active groups are generated on the surface of the wear-resistant reinforcing agent, which can not only improve its bonding force with PETG resin, but also optimize the surface structure, reduce the friction coefficient, and further enhance the wear resistance; The second modified wear-resistant enhancer is immersed in a silane coupling agent solution with a mass fraction of 5-10% for 3-5 hours, and then taken out and dried. The silane coupling agent can form a chemical bond between the wear-resistant enhancer and the PETG resin to enhance the interface compatibility, ensure that the wear-resistant enhancer can play a stable role during the use of the material, and continuously improve the wear resistance of the material.

[0009] Preferably, the corrosion resistant additive may also be replaced by a modified corrosion resistant additive, and the preparation process of the modified corrosion resistant additive includes: The compounded corrosion-resistant additive is mixed with a zwitterionic surfactant accounting for 3-8% of the total mass under high-speed stirring at a stirring speed of 500-800 r / min for 15-30 minutes. The zwitterionic surfactant can reduce the interfacial tension between the additives, enhance the dispersion uniformity of each component, and improve the synergistic corrosion-resistant effect; The mixed system is placed in an ultrasonic environment for treatment, with an ultrasonic frequency of 40-60kHz and an ultrasonic time of 20-40 minutes, and the cavitation effect of ultrasound is used to further refine the additive particles, increase their specific surface area, and improve the contact area and bonding force with the PETG resin, thereby enhancing the corrosion resistance of the material; Add 2-5% nano-carbon fiber of the total mass to the corrosion-resistant additive system after ultrasonic treatment, and melt blend for 20-30 minutes at 120-150°C and a screw speed of 150-250r / min. The nano-carbon fiber has excellent mechanical properties and chemical stability, and can form a reinforced network structure in the corrosion-resistant additive system to improve the overall stability and corrosion resistance durability.

[0010] A method for preparing an impact-resistant modified PETG polyester material comprises the following steps: Weigh PETG resin, impact modifier, wear enhancer, stabilizer, lubricant, modified corrosion resistant additive and antioxidant according to weight; Add the weighed components into a high-speed mixer, mix at 80-120°C and 300-500 r / min for 10-20 minutes to obtain a premix; The premix is ​​added into a twin-screw extruder, and the temperature of the twin-screw extruder from the feeding section to the die head is set to 200-220° C., 220-240° C., 230-260° C., and 250-270° C. in sequence, and melt blended at a screw speed of 300-500 r / min and an aspect ratio of 30-40, and extruded into granules to obtain an impact-modified PETG polyester material; The granulated material is dried in a forced air drying oven at 60-80°C for 4-6 hours to further remove moisture and low molecular weight volatiles.

[0011] Preferably, before the premixing step, the nano-silica is surface treated by using silane coupling agent KH-550, with a mass ratio of nano-silica to silane coupling agent of 100:1-3, and reacting at 80-100° C. for 1-2 hours under high-speed stirring to enhance its compatibility with other components.

[0012] It has the following beneficial effects: The impact-resistant modified PETG polyester material and the preparation method thereof are prepared by scientifically mixing PETG The proportion of key ingredients such as resin and impact modifier, as well as the innovative modification of wear-resistant enhancers and corrosion-resistant additives, optimize the internal structure of the material and enhance the intermolecular force, so that it has stronger energy absorption and dispersion capabilities. When impacted by external forces, the material can effectively buffer the impact energy, greatly reduce the risk of rupture, significantly improve its own toughness and durability, and greatly improve the surface hardness of the material, make the organizational structure more dense, and effectively resist external friction. This makes the wear degree of the material significantly reduced during long-term use, greatly prolongs the service life, and reduces the maintenance and replacement costs caused by wear. Through special treatment of corrosion-resistant additives and optimization of the overall formula, a stable and dense protective barrier is formed on the surface of the material, which effectively blocks the erosion of corrosive media such as acids, alkalis, and salts. Through the optimization of the formula and process, a stable antioxidant system is formed inside the material, which effectively inhibits the generation of free radicals and the progress of oxidation reactions. This enables the material to maintain good performance stability under high temperature and oxidative environment, effectively resist oxidative degradation, delay the aging and brittle process, significantly prolong the service life of the material, and improve the reliability of the product. DETAILED DESCRIPTION

[0013] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0014] In the first embodiment, the present invention provides a technical solution: an impact-modified PETG polyester material, comprising the following components: 50 parts of PETG resin, 10 parts of impact modifier, 5 parts of wear-resistant enhancer, 1 part of stabilizer, 1 part of lubricant, 2 parts of corrosion-resistant additive, and 1 part of antioxidant; A method for preparing an impact-resistant modified PETG polyester material comprises the following steps: Weigh PETG resin, impact modifier, wear enhancer, stabilizer, lubricant, modified corrosion resistant additive and antioxidant according to weight; The weighed components were added into a high-speed mixer and mixed at 80°C and 300 r / min for 10 minutes to obtain a premix; The premix is ​​added into a twin-screw extruder, and the temperature of the twin-screw extruder from the feeding section to the die head is set to 200° C., 220° C., 230° C., and 250° C. in sequence, and melt blended at a screw speed of 300 r / min and an aspect ratio of 30, and extruded into granules to obtain an impact-modified PETG polyester material; The granulated material was dried in a forced air drying oven at 60° C. for 4 hours to further remove moisture and low molecular weight volatiles.

[0015] In the second embodiment, the present invention provides a technical solution: an impact-modified PETG polyester material, comprising the following components: 65 parts of PETG resin, 20 parts of impact modifier, 10 parts of wear-resistant enhancer, 3 parts of stabilizer, 2 parts of lubricant, 5 parts of corrosion-resistant additive, and 2 parts of antioxidant; A method for preparing an impact-resistant modified PETG polyester material comprises the following steps: Weigh PETG resin, impact modifier, wear enhancer, stabilizer, lubricant, modified corrosion resistant additive and antioxidant according to weight; The weighed components were added into a high-speed mixer and mixed at 100°C and 400 r / min for 15 minutes to obtain a premix; The premix is ​​added into a twin-screw extruder, and the temperature of the twin-screw extruder from the feeding section to the die head is set to 210° C., 230° C., 245° C., and 260° C. in sequence, and melt blended at a screw speed of 400 r / min and an aspect ratio of 35, and extruded into granules to obtain an impact-modified PETG polyester material; The granulated material was dried in a forced air drying oven at 70° C. for 5 hours to further remove moisture and low molecular weight volatiles.

[0016] In the third embodiment, the present invention provides a technical solution: an impact-modified PETG polyester material, comprising the following components: 80 parts of PETG resin, 30 parts of impact modifier, 15 parts of wear-resistant enhancer, 5 parts of stabilizer, 3 parts of lubricant, 8 parts of corrosion-resistant additive, and 3 parts of antioxidant; A method for preparing an impact-resistant modified PETG polyester material comprises the following steps: Weigh PETG resin, impact modifier, wear enhancer, stabilizer, lubricant, modified corrosion resistant additive and antioxidant according to weight; The weighed components were added into a high-speed mixer and mixed at 120°C and 500 r / min for 20 minutes to obtain a premix; The premix is ​​added into a twin-screw extruder, and the temperature of the twin-screw extruder from the feeding section to the die head is set to 220° C., 240° C., 260° C., and 270° C. in sequence, and melt blended at a screw speed of 500 r / min and an aspect ratio of 40, and extruded into granules to obtain an impact-modified PETG polyester material; The granulated material was dried in a forced air drying oven at 80°C for 6 hours to further remove moisture and low molecular weight volatiles.

[0017] In a fourth embodiment, the present invention provides a technical solution: on the basis of the first embodiment, the wear-resistant reinforcing agent is replaced with a modified wear-resistant reinforcing agent, and the preparation process of the modified wear-resistant reinforcing agent includes: The compounded wear-resistant reinforcing agent was mixed with carbon nanotubes accounting for 2% of the total mass, and mixed for 20 minutes at 100° C. and a screw speed of 180 r / min; The wear-resistant reinforcing agent after the first modification is subjected to plasma treatment, and more active groups are generated on the surface of the wear-resistant reinforcing agent under the conditions of a radio frequency power of 120 W and a treatment time of 15 minutes; The second modified wear-resistant reinforcing agent was immersed in a silane coupling agent solution with a mass fraction of 5% for 3 hours, and then taken out and dried.

[0018] In a fifth embodiment, the present invention provides a technical solution: on the basis of the second embodiment, the wear-resistant reinforcing agent is replaced with a modified wear-resistant reinforcing agent, and the preparation process of the modified wear-resistant reinforcing agent includes: The compounded wear-resistant reinforcing agent was mixed with carbon nanotubes accounting for 4% of the total mass, and mixed for 25 minutes at 115° C. and a screw speed of 210 r / min; The wear-resistant reinforcing agent after the first modification is subjected to plasma treatment, and more active groups are generated on the surface of the wear-resistant reinforcing agent under the conditions of a radio frequency power of 150 W and a treatment time of 20 minutes; The second modified wear-resistant reinforcing agent was immersed in a silane coupling agent solution with a mass fraction of 7% for 4 hours, and then taken out and dried.

[0019] In the sixth embodiment, the present invention provides a technical solution: on the basis of the third embodiment, the wear-resistant reinforcing agent is replaced with a modified wear-resistant reinforcing agent, and the preparation process of the modified wear-resistant reinforcing agent includes: The compounded wear-resistant reinforcing agent was mixed with carbon nanotubes accounting for 6% of the total mass, and mixed for 30 minutes at 130°C and a screw speed of 250 r / min. The wear-resistant reinforcing agent after the first modification is subjected to plasma treatment, and more active groups are generated on the surface of the wear-resistant reinforcing agent under the conditions of a radio frequency power of 180 W and a treatment time of 25 minutes; The second modified wear-resistant reinforcing agent was immersed in a silane coupling agent solution with a mass fraction of 10% for 5 hours, and then taken out and dried.

[0020] In the seventh embodiment, the present invention provides a technical solution: on the basis of the fourth embodiment, the corrosion-resistant additive is replaced with a modified corrosion-resistant additive, and the preparation process of the modified corrosion-resistant additive includes: The compounded corrosion-resistant additive and the zwitterionic surfactant accounting for 3% of the total mass are mixed under high-speed stirring at a stirring speed of 500 r / min for 15 minutes; The mixed system was placed in an ultrasonic environment for treatment, with an ultrasonic frequency of 40 kHz and an ultrasonic time of 40 minutes; To the anti-corrosion additive system after ultrasonic treatment, carbon nanofibers accounting for 2% of the total mass were added, and melt blended at 120° C. and a screw speed of 150 r / min for 20 minutes.

[0021] In the eighth embodiment, the present invention provides a technical solution: based on the fifth embodiment, the corrosion-resistant additive is replaced with a modified corrosion-resistant additive, and the preparation process of the modified corrosion-resistant additive includes: The compounded corrosion-resistant additive and the zwitterionic surfactant accounting for 5% of the total mass are mixed under high-speed stirring at a stirring speed of 650 r / min for 23 minutes; The mixed system was placed in an ultrasonic environment for treatment, with an ultrasonic frequency of 50 kHz and an ultrasonic time of 30 minutes; To the anti-corrosion additive system after ultrasonic treatment, 3.5% of nano-carbon fiber was added, and the mixture was melt-blended at 135° C. and a screw speed of 200 r / min for 25 minutes.

[0022] In a ninth embodiment, the present invention provides a technical solution: based on the sixth embodiment, the corrosion-resistant additive is replaced with a modified corrosion-resistant additive, and the preparation process of the modified corrosion-resistant additive includes: The compounded corrosion-resistant additive and the zwitterionic surfactant accounting for 5% of the total mass are mixed under high-speed stirring at a stirring speed of 650 r / min for 23 minutes; The mixed system was placed in an ultrasonic environment for treatment, with an ultrasonic frequency of 50 kHz and an ultrasonic time of 30 minutes; To the anti-corrosion additive system after ultrasonic treatment, 5% of the total mass of nano-carbon fibers were added, and melt-blended at 135° C. and a screw speed of 200 r / min for 25 minutes.

[0023] Impact resistance test: According to the standard requirements, the prepared impact-resistant modified PETG polyester material is processed into a standard specimen with a size of 80mm×10mm×4mm. The specimen is installed on the fixture of the cantilever beam impact testing machine to ensure that the specimen is firmly installed. The pendulum is released to impact the specimen, and the impact energy absorbed when the specimen breaks is recorded. Each group of tests is tested at least 5 times in parallel, and the average value is taken as the impact resistance result of this group of specimens.

[0024] Wear resistance test: The impact-modified PETG polyester material is processed into a circular specimen with a diameter of 50 mm and a thickness of 5 mm. The initial mass m1 of the specimen is accurately weighed with an electronic balance, and the specimen is mounted on an abrasion testing machine. The abrasion test conditions are set, and the abrasion testing machine is started to rub the specimen against the abrasive. After the test, the specimen is removed, and the surface debris is cleaned with a brush. The mass m2 of the specimen is weighed with an electronic balance, and the mass loss Δm=m1-m2 of the specimen is calculated to evaluate the wear resistance of the material. At least 5 parallel tests are carried out for each group of tests, and the average value is taken as the wear resistance result of the group of specimens.

[0025] Corrosion resistance test: The impact-modified PETG polyester material was processed into a square specimen with a size of 50mm×50mm×3mm. The initial mass m1 of the specimen was accurately weighed with an electronic balance, and the initial appearance of the specimen was recorded. The specimens were immersed in different corrosive media, and a group of blank control specimens were set up at the same time. They were immersed in deionized water. The container containing the specimens was placed in a constant temperature and humidity chamber, and the temperature was set to 50℃, the humidity was set to 90%, and the immersion time was 7 days. After the immersion, the specimens were taken out, rinsed with deionized water, and the surface moisture was absorbed with filter paper. The mass m2 of the specimens was weighed with an electronic balance, and the appearance changes of the specimens were recorded. The partially immersed specimens were subjected to a tensile test on a universal material testing machine, and their tensile strength and elongation at break were measured. The specimens were compared with the original specimens that were not immersed, and the changes in the mechanical properties of the materials in the corrosive medium were evaluated. According to the changes in the mass, appearance, and mechanical properties of the specimens, the corrosion resistance of the materials was comprehensively evaluated. At least 5 parallel tests were conducted for each group of tests, and the average value was taken as the corrosion resistance result of the group of specimens.

[0026] Antioxidant performance test: Take an appropriate amount of impact-modified PETG polyester material, make it into powder, accurately weigh 5-10 mg of the sample, put it into the crucible of the thermogravimetric analyzer, set the test conditions of the thermogravimetric analyzer, such as the heating rate is 10℃ / min, the test temperature range is from room temperature to 600℃, the atmosphere is air, start the thermogravimetric analyzer, record the mass change of the sample during the heating process, and analyze the material's initial oxidation temperature (i.e. the temperature when the mass begins to drop significantly), the maximum oxidation rate temperature, and the mass residual rate at a certain temperature according to the mass change curve, so as to evaluate the material's antioxidant performance. At least 3 parallel tests are carried out for each group of tests, and the average value is taken as the antioxidant performance result of the group of samples.

[0027] The test form is as follows:

[0028] According to the above test data, it can be seen that the eighth embodiment is the best embodiment of the present invention.

[0029] Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field and related fields without creative work should fall within the scope of protection of the present invention. The structures, devices and operating methods not specifically described and explained in the present invention are implemented according to the conventional means in the field unless otherwise specified and limited.

Claims

1. An impact-resistant modified PETG polyester material, characterized in that: It includes the following components: 50-80 parts of PETG resin, 10-30 parts of impact modifier, 5-15 parts of wear-resistant enhancer, 1-5 parts of stabilizer, 1-3 parts of lubricant, 2-8 parts of corrosion-resistant additive, and 1-3 parts of antioxidant; The wear-resistant reinforcing agent is a compound of ultra-high molecular weight polyethylene micropowder, nano-ceramic particles and polytetrafluoroethylene micropowder, and the compounding ratio range is 1:1:2; The wear-resistant enhancer can also be replaced by a modified wear-resistant enhancer, and the preparation process of the modified wear-resistant enhancer includes: The compounded wear-resistant reinforcing agent is mixed with carbon nanotubes accounting for 2-6% of its total mass, and mixed for 20-30 minutes at 100-130°C and a screw speed of 180-250r / min. The carbon nanotubes have extremely high strength and modulus, and can form a three-dimensional reinforcement network in the wear-resistant reinforcing agent system, significantly improving the material's ability to resist wear; The wear-resistant reinforcing agent after the first modification is subjected to plasma treatment. Under the conditions of RF power of 120-180W and treatment time of 15-25 minutes, more active groups are generated on the surface of the wear-resistant reinforcing agent, which can not only improve its bonding force with PETG resin, but also optimize the surface structure, reduce the friction coefficient, and further enhance the wear resistance; The second modified wear-resistant enhancer is immersed in a silane coupling agent solution with a mass fraction of 5-10% for 3-5 hours, and then taken out and dried. The silane coupling agent can form a chemical bond between the wear-resistant enhancer and the PETG resin to enhance the interface compatibility, ensure that the wear-resistant enhancer can play a stable role during the use of the material, and continuously improve the wear resistance of the material.

2. The impact-resistant modified PETG polyester material according to claim 1, characterized in that: The impact modifier is compounded from methyl methacrylate-butadiene-styrene copolymer, acrylonitrile-butadiene-styrene copolymer and ethylene-octene copolymer, and the compounding ratio range is 1:1:

3.

3. The impact-modified PETG polyester material according to claim 1, characterized in that: The stabilizer is an organic tin stabilizer, and the lubricant is ethylene bisstearamide.

4. The impact-resistant modified PETG polyester material according to claim 1, characterized in that: The corrosion-resistant additive is prepared by compounding fluorine-containing polymer, nano-silicon dioxide and phosphate compounds, and the compounding ratio is 1:1:

3.

5. The impact-resistant modified PETG polyester material according to claim 4, characterized in that: The corrosion-resistant additive may also be replaced by a modified corrosion-resistant additive, and the preparation process of the modified corrosion-resistant additive includes: The compounded corrosion-resistant additive is mixed with a zwitterionic surfactant accounting for 3-8% of the total mass under high-speed stirring at a stirring speed of 500-800 r / min for 15-30 minutes. The zwitterionic surfactant can reduce the interfacial tension between the additives, enhance the dispersion uniformity of each component, and improve the synergistic corrosion-resistant effect; The mixed system is placed in an ultrasonic environment for treatment, with an ultrasonic frequency of 40-60kHz and an ultrasonic time of 20-40 minutes, and the cavitation effect of ultrasound is used to further refine the additive particles, increase their specific surface area, and improve the contact area and bonding force with the PETG resin, thereby enhancing the corrosion resistance of the material; Add 2-5% nano-carbon fiber of the total mass to the corrosion-resistant additive system after ultrasonic treatment, and melt blend for 20-30 minutes at 120-150°C and a screw speed of 150-250r / min. The nano-carbon fiber has excellent mechanical properties and chemical stability, and can form a reinforced network structure in the corrosion-resistant additive system to improve the overall stability and corrosion resistance durability.

6. A method for preparing an impact-modified PETG polyester material, characterized in that: The steps include: Weigh PETG resin, impact modifier, wear enhancer, stabilizer, lubricant, modified corrosion resistant additive and antioxidant according to weight; Add the weighed components into a high-speed mixer, mix at 80-120°C and a speed of 300-500 r / min for 10-20 minutes to obtain a premix; The premix is ​​added into a twin-screw extruder, and the temperature of the twin-screw extruder from the feeding section to the die head is set to 200-220° C., 220-240° C., 230-260° C., and 250-270° C. in sequence, and melt blended at a screw speed of 300-500 r / min and an aspect ratio of 30-40, and extruded into granules to obtain an impact-modified PETG polyester material; The granulated material is dried in a forced air drying oven at 60-80°C for 4-6 hours to further remove moisture and low molecular weight volatiles.

7. The method for preparing an impact-modified PETG polyester material according to claim 6, characterized in that: Before the premixing step, the nano-silica is surface treated by using silane coupling agent KH-550, with a mass ratio of nano-silica to silane coupling agent of 100:1-3, and reacting at 80-100°C for 1-2 hours under high-speed stirring to enhance its compatibility with other components.

Citation Information

Patent Citations

  • Low-noise high-wear-resistance modified copolyester as well as preparation method and application thereof

    CN118620359A

  • PETG material for optical mirror surface material and preparation method of PETG material

    CN119241999A